Analysis of Factors Associated with Adolescent Mental Health in the School Environment - Agnesia, Yoana; Nur Zakiyah , Tiara; Safriani , Lili (Journal of Engineering Science and Technology Management, 2025)
Adolescence is an important transition phase from childhood to adulthood which is marked by physical, emotional and social changes. At this stage, teenagers are in the process of searching for their identity so they are very vulnerable to the influence of the environment, peers and social media. Lack of self-control, minimal understanding of the risks of dangerous behavior such as promiscuity, smoking and drug abuse, as well as weak parental attention and moral education further increase teenagers' vulnerability to risky behavior. Indonesian adolescent mental health data for 2024 shows that one in three adolescents, or around 15.5 million individuals, experienced mental health problems in the last 12 months, with anxiety disorders being the most common cases (28.2% of girls and 25.4% of boys). In addition, around 2.45 million teenagers experience at least one mental disorder. Factors such as academic pressure, family relationship dynamics, bullying, gadget addiction, and socio-economic conditions also influence their mental health conditions. This research on adolescent mental health aims to provide education and prevention efforts against risky behavior that can damage physical and mental health. Through this educational activity, it is hoped that teenagers will have a better understanding of the consequences of their actions, be able to maintain mental health, and build strong character to face future challenges positively.